(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The article describes in detail the needs of people in joint activities - relationships, interactions, information and their joint activities to exchange information. It is especially emphasized that when forming personal communication, it is necessary to take into account his age, gender, profession, worldview.